2014
DOI: 10.1080/02755947.2014.944679
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Paddlefish Reintroduction into Allegheny Reservoir

Abstract: Gillnetting and radiotelemetry were used to evaluate the reintroduction of Paddlefish Polyodon spathula into Allegheny Reservoir, New York–Pennsylvania. Gillnetting produced 86 total captures over 6,943 h of effort in the spring and early summer of 2008–2011. Forty‐four of these individuals received implanted radio transmitters and were tracked from May 2008 to August 2011. Paddlefish showed a strong preference for reservoir sections where depths ranged from 6 to 18 m; only one individual was located in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Increased age‐0 recruitment to adulthood resulting from warmer Spring temperatures would increase adult abundance, in turn increasing catch rates, as in a previous study that found relationships between water temperature and paddlefish catch rates (Lein & Devries, 1998). Since paddlefish spawning success (Runstrom et al, 2001) and spawning timing in late May early June (Ruelle & Hudson, 1977) is related to discharge, and suitable preferred habitat (i.e., water depth 6–18 m; Budnik et al, 2014) requires moderate flows (Phelps et al, 2009), dam operations providing these flows may benefit the Gavins Point paddlefish population.…”
Section: Discussionmentioning
confidence: 99%
“…Increased age‐0 recruitment to adulthood resulting from warmer Spring temperatures would increase adult abundance, in turn increasing catch rates, as in a previous study that found relationships between water temperature and paddlefish catch rates (Lein & Devries, 1998). Since paddlefish spawning success (Runstrom et al, 2001) and spawning timing in late May early June (Ruelle & Hudson, 1977) is related to discharge, and suitable preferred habitat (i.e., water depth 6–18 m; Budnik et al, 2014) requires moderate flows (Phelps et al, 2009), dam operations providing these flows may benefit the Gavins Point paddlefish population.…”
Section: Discussionmentioning
confidence: 99%